2012
DOI: 10.1111/j.1752-0606.2012.00310.x
|View full text |Cite
|
Sign up to set email alerts
|

Centering The Voices Of International Students In Family Studies And Family Therapy Graduate Programs

Abstract: In this article, we report the results of a survey that accessed the perceptions of family studies and family therapy international master's and doctoral students across the United States. Our goals included giving collective voice to the experience of international students and gathering their suggestions for improving programs. Themes that emerged from responses to open- and closed-ended questions included feeling (mis)understood and (de)valued; forming personal connections and experiencing marginalization; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Previous research suggested that language was a primary barrier that international students face in the United States (Bresnahan & Cai, ; McDowell et al, ; Mori, ; Zhai, ). Our results are consistent with those of McLachlan and Justin () who reported that international students had difficulty acculturating due to their relatively low English language ability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research suggested that language was a primary barrier that international students face in the United States (Bresnahan & Cai, ; McDowell et al, ; Mori, ; Zhai, ). Our results are consistent with those of McLachlan and Justin () who reported that international students had difficulty acculturating due to their relatively low English language ability.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived discrimination is the subjective view that one has been treated unjustly because of racial or ethnic reasons (Major, Quinton, & McCoy, ). International students report experiencing perceived discrimination in the United States (Lee & Rice, ; McDowell et al, ; McLachlan & Justin, ; Mittal & Wieling, ; Wadsworth, Hecht, & Jung, ). International students from non‐European countries experience more perceived discrimination than those from European countries because of the difference in their appearance (Hanassab, ; Hanassab & Tidewell, ; Poyrazli & Lopez, ; Yeh & Inose, ).…”
Section: Acculturation Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The first year for ISCSs is often used to gain familiarity with the American culture, teaching, and learning style. This is evidenced by reports of international students' adjustment struggles with acculturation (Hanassab & Tidewell, 2002;Hirai, Frazier, & Syed, 2015;McDowell, Fang, Kosutic, & Griggs, 2012). To further complicate issues, most of the ISCSs (like their domestic colleagues) have the responsibility of finding school sites for field experience.…”
Section: Challenges Iscss Face In Us School Counseling Training Promentioning
confidence: 99%
“…Acculturation to the U.S. culture has proven to be a significant source of stress for most international students. Adjustment (McDowell et al, 2012), psychological and sociocultural (Hirai, et al, 2015), and academic challenges (Hanassab & Tidewell, 2002) are among some of the documented acculturative stresses. International counseling students are not exempt from these identified acculturative stresses (Behl et al, 2017).…”
Section: Challenges Iscss Face In Us School Counseling Training Promentioning
confidence: 99%